Introduction to Bioethanol Lab on Cassava for Biology Education Students at UIN Jakarta - Najwa Syafkitamsana; Solihin Solihin; Ria Ria; Septiandita Mailayfaiza (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study discusses conventional bioethanol production through fermentation as a response to the need for environmentally friendly alternative energy sources. The objectives of this practicum are to understand the basic principles of fermentation, identify the factors that influence it, carry out a simple fermentation process using natural materials (sugar/corn/cassava) and Saccharomyces cerevisiae yeast, and analyze the results. The methods used include preparing a sugar solution, inoculating yeast, anaerobic incubation at 30–35 °C for 2–5 days, observing CO₂ formation, filtration, and simple purification through distillation. The study employed an experimental design, with 63 biology education students participating. The results of the practicum indicate that students understand the success rate of bioethanol fermentation, as evidenced by the formation of CO₂ bubbles and the feasibility of ethanol separation by distillation. Students can understand the factors that influence conventional bioethanol production.